Frontiers of Knowledge: An Interview with 2017 Edward Novitski Prize Recipient Jonathan Hodgkin - Hodgkin, Jonathan (Genetics, 2017)
The Genetics Society of America’s Edward Novitski Prize recognizes a single experimental accomplishment or a body of work in which an exceptional level of creativity and intellectual ingenuity has been used to design and execute scientific experiments to solve a difficult problem in genetics. The 2017 winner, Jonathan Hodgkin, used elegant genetic studies to unravel the sex determination pathway in Caenorhabditis elegans. He inferred the order of genes in the pathway and their modes of regulation using epistasis analyses—a powerful tool that was quickly adopted by other researchers. He expanded the number and use of informational suppressor mutants in C. elegans that are able to act on many genes. He also introduced the use of collections of wild C. elegans to study naturally occurring genetic variation, paving the way for SNP mapping and QTL analysis, as well as studies of hybrid incompatibilities between worm species. His current work focuses on nematode–bacterial interactions and innate immunity.